Discrete Element Method Simulation of Borehole Breakout Based on the Strain Energy Concept. Issue 1 (1st January 2023) - Xiang, Z; Oh, J; Moon, T; Si, G; Li, X; Canbulat, I
Abstract: This study focused on studying the V-shaped rock failure around borehole walls and reproducing borehole breakout using numerical simulations. Discrete element method (DEM) is adopted, and a two-dimensional particle flow code (PFC2D) model is built based on Tenino sandstone. The simulations are conducted by applying different maximum horizontal stress values under the same minimum horizontal stress condition, and the results are compared with the true-triaxial breakout experiments on the same rock properties and loading conditions. Due to the absence of vertical stress in 2D simulations, the obtained angular spans are generally larger than the experimental values. On the other hand, the breakout depths are found to be significantly smaller than the experimental results since the failed particles within the breakout zone remained to withstand internal loads and constrain the damage zone. In order to better simulate the rock detachment process during breakout formation, a particle removal algorithm using the strain energy release concept is developed and embedded into the model. With the implementation of the algorithm, the breakout propagation process in the vicinity of the borehole shows a good agreement with the experimental observations, suggesting that the effective removal of failed particles is essential for accurately simulating borehole breakout. The results from this study can provide new insights into the V-shaped breakout formation mechanism and strain energy changes during borehole breakout initiation and propagation.